Design of an intranet radio using real time transport protocol for university campus - Matshanga, Nsindiso Mnqobi (Midlands State University, 2018)
The dissipation of information is an essential aspect of any community. The advent of media services such as television and radio has improved the way information has been broadcasted to the general public. Unfortunately in Zimbabwe Universities, these services have not yet been utilized. This Dissertation illustrates a prototype of campus radio streaming system over an intranet. This is to provide local universities with a cheaper alternative to providing a local radio station compared to the traditional terrestrial radio. The project demonstrates a system using application layer routing for real time audio streaming which takes advantage of the already existing network infrastructure. This system could be used to build a local radio station for universities.